2012
DOI: 10.4254/wjh.v4.i9.262
|View full text |Cite
|
Sign up to set email alerts
|

Centrilobular necrosis in acute presentation of Japanese patients with type 1 autoimmune hepatitis

Abstract: CN is observed in both Japanese patients with acute hepatitis phase and acute exacerbation phase of type 1 AIH, although AIH with CN often shows clinical features of the genuine acute form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Compared with other histological features reported previously, the present data show both similarities and broad differences as follows (our data vs other studies): hepatic rosette formation (60.5% vs 14.6–55.6%),22 24 27 34 35 58 interface hepatitis (75% vs 66.7–92.3%),5 22 35 36 42 58 bile duct injury (50% vs 21.1–77.8%),22 58 fibrosis (67.4% vs 40–96.1%),5 6 16 22 34 36 42 67 end-stage fibrosis (stage 4) (0% vs 0–33.3%),5–7 14 16 42 portal inflammation (92.9% vs 90–100%),16 22 35 lobular necrosis/inflammation (97.7% vs 73–100%)5 16 22 27 42 67 and cobblestone appearance of hepatocytes (82.6% vs 44.4%, 8/18 cases) 27. It is worth noting that the frequencies of fibrosis and interface hepatitis varied markedly among studies, which may have led to controversial conclusions in the clinicopathological characteristics of AIH with acute presentations compared with classic AIH.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Compared with other histological features reported previously, the present data show both similarities and broad differences as follows (our data vs other studies): hepatic rosette formation (60.5% vs 14.6–55.6%),22 24 27 34 35 58 interface hepatitis (75% vs 66.7–92.3%),5 22 35 36 42 58 bile duct injury (50% vs 21.1–77.8%),22 58 fibrosis (67.4% vs 40–96.1%),5 6 16 22 34 36 42 67 end-stage fibrosis (stage 4) (0% vs 0–33.3%),5–7 14 16 42 portal inflammation (92.9% vs 90–100%),16 22 35 lobular necrosis/inflammation (97.7% vs 73–100%)5 16 22 27 42 67 and cobblestone appearance of hepatocytes (82.6% vs 44.4%, 8/18 cases) 27. It is worth noting that the frequencies of fibrosis and interface hepatitis varied markedly among studies, which may have led to controversial conclusions in the clinicopathological characteristics of AIH with acute presentations compared with classic AIH.…”
Section: Discussionsupporting
confidence: 73%
“…Although patients with histological features of acute liver failure (submassive or massive necrosis) were not included in the present study, cases with these histological patterns have repeatedly been reported 24 25 27–29 42. Portal inflammation was almost always found, accounting for 92.9% of our patients (90–100% in other studies),16 22 35 including in early-biopsy cases with a mild lobular injury and without any evidence of disease chronicity. Accordingly, AIH with acute presentations can present in a wide histological spectrum of acute hepatitis.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Patients with severe acute hepatitis or FHF may have autoantibodies in lowtiter or absence of conventional autoantibodies. They may also have normal gammaglobulin or IgG levels and atypical histological find ings, including zone III centrolobular necrosis, perivenullar or central inflammation with lymphocytes and plasma cells, multiacinar collapse and lymphoid aggregates (9,35,36) . Diagnostic scoring systems can aid in the diagnosis of these peculiar types of AIH, but it should be kept in mind that they have been standardized in cohorts of subjects with classical AIH.…”
Section: Diagnosismentioning
confidence: 99%